Clasificación de los murciélagos de la región de los Tuxtlas, Veracruz, respecto a su respuesta a la fragmentación del hábitat - Galindo González, Jorge (Instituto de Ecología, A.C., 2020)
I propose three types of bat species according to their response to habitat fragmentation in Los Tuxtlas region: Type I (habitat dependent), Type II (vulnerable), and Type III (adaptable). Effects of habitat fragmentation on bat genetic structure will be primarily patent on Type I bats, and the major effect will be observed at long term.